Phylogenetic analysis of influenza A viruses (H1N1)pdm circulating during 2014–2015 epidemic season in Ukraine - Radchenko, L.V.; Smutko, O.Yu.; Fesenko, A.Yu.; Mironenko, A.P. (Вiopolymers and Cell, 2016)
Aim. To analyze the pandemic influenza A(H1N1) strains that circulated in Ukraine during 2014–2015 epidemic season. Methods. Real-time polymerase chain reaction (RT-PCR). The phylogenetic trees were constructed using MEGA 6 software. Results. The strains, that were circulating in Ukraine were similar to those of the A/California/07/2009 (H1N1) vaccine strain. Most strains belonged to the clade 6B. The H275Y mutation in the neuraminidase (NA) gene was identified, that confers resistance to oseltamivir. Conclusions. Based on the nucleotide sequences of HA and NA genes, we constructed the influenza virus phylogenetic trees. The influenza virus isolated in 2014–2015 epidemic season had a specific mutation, associated with resistance to antiviral drugs such as oseltamivir. Мета. Молекулярний та філогенетичний аналіз пандемічних вірусів грипу A(H1N1), що циркулювали в Україні протягом сезо-ну 2014-2015 років. Методи. Зразки були проаналізовані методом полімеразної ланцюгової реакції (ПЛР) в реальному часі. Філогенетичні дерева будували в програмі MEGA 6. Результати. Сиквенси українських ізолятів вірусів грипу A(H1N1)pdm були подібними до вакцинного штаму A/California/07/2009. Більшість штамів належали до кладу 6В. Серед досліджуваних ізолятів виявили мутацію H275Y в гені нейрамінідази, яка зумовлює стійкість до озельтамівіру. Висновки. Базуючись на сиквенсах генів HA і NA вірусів грипу побудували філогенетичні дерева. Український вірус, виділений в сезоні 2014-2015 років мав специфічну мутацію, яку асоціюють з стійкістю до противірусних препаратів, таких як озельтамівір. Цель. Молекулярный и филогенетический анализ пандемических вирусов гриппа A(H1N1), которые циркулировали в Украине на протяжении 2014-2015 годов. Методы. Образцы были проанализированы методом полимеразной цепной реакции (ПЦР) в реальном времени. Филогенетические деревья построили в программе MEGA 6. Результаты. Сиквенсы украинских изолятов вирусов гриппа A(H1N1)pdm были подобными к вакцинному штамму A/California/07/2009. Большинство штаммов принадлежа-ли к клайду 6В. Среди исследованных изолятов обнаружили мутацию H275Y в гене нейраминидазы. Выводы. Основываясь на сиквенсах генов HA и NA вирусов гриппа, построили филогенетические деревья. Украинский вирус, изолированный в сезоне 2014-2015 годов имел специфическую мутацию, которую ассоциируют с устойчивостью к противовирусным препаратам, таким как осельтамивир.